Cytokine status in posttraumatic synovitis on the background of systemic and intra-articular use of NSAID and ozone - G. V. Poryadin; A. N. Zakhvatov; T. V. Tarasova; D. A. Khaydar; V. O. Timoshkin (Медицинская иммунология, 2020)
Joint  damage  initiates aseptic  self-sustaining inflammation, which  contributes the  progression of post-traumatic destruction of tissues  not  only  in the  pathological focus,  but  also outside  it,  significantly expanding the zone of degenerative changes due to secondary alterations. One of the leading roles in pathogenesis of the inflammation belongs  to secreted  mediators-cytokines – that  impart to the cells the proinflammatory potential and  promote the  long-term inflammation. These  effects  lead  to  disorganization of extracellular matrix and progressive  disintegration of cartilage.  In this regard,  the development and implementation of new pathogenetic treatment methods of post-traumatic synovitis permits  to limit the area of secondary alterations and activate  reparative mechanisms in the lesion  from the early terms,  thus potentially improving the results of  rehabilitation treatment and  increasing efficiency  of  conventional therapy   in  post-traumatic synovitis. Numerous experimental and  clinical  studies  have proven  the  effectiveness and  safety of ozone  therapy, e.g., in degenerative joint  diseases.  Despite extensive  data  highlighting effectiveness of ozone  therapy  in articular pathology, the  study of cytokine profile  when  using this treatment of posttraumatic synovitis  was performed only in few works, thus emphasizing the prospects for further research in this direction. The study was aimed for investigation of cytokine status in the patients with posttraumatic synovitis subjected to intravenous and intraarticular ozone  therapy  in combination with intra-articular administration of xefocam.The  work is based  on  the  results  of examination and  treatment of 69 patients with  traumatic injuries  of the  knee  joint,  complicated by development of  post-traumatic synovitis.  Two  study  groups  were  formed, comparable in volume  and  type  of joint  injury.  The  patients from  group  I (35 cases)  received  conventional combined treatment. Among  the  mandatory measures, evacuation of a synovial-hemorrhagic punctate was performed from the cavity of damaged joint. Conservative therapy included NSAIDs, medications that improve microcirculation, at standard dosages, as well as physical therapy. In group II (34 patients), traditional therapy was supplemented with a 10-day  course of intravenous injectable ozone  therapy  with 200 ml of NaCl  solution at a concentration of 2.0 mg/l daily and intra-articular ozone injection at a concentration of 5 mg/l in a volume of 20 ml 5 times  in a day. During arthroscopy, lavage of the joint  cavity was performed with ozonated saline solution at a concentration of 2.0 mg/l.  The ozone  therapy  was combined with three  intra-articular injections of xefocam  at a dose of 8 mg, once  every 4 days. A patent for the  invention was obtained for this treatment technology (No.  2456988 of 27.07.12).  The cytokine profile was evaluated by the content of Pro-inflammatory (TNFα, IL-1β, IL-6, IL-17), regulatory (IL-2), Il-1β receptor antagonist, and anti-inflammatory (IL-4, IL-10) cytokines by solid-phase enzyme  immunoassay with an indicator label in the  form  of peroxidase. Statistical analysis of the results was carried  out using the Student criterion. Combined therapy  of intravenous and intraarticular ozone therapy  in combination with intra-articular injections of xefocam  contributed to the inhibition of the  inflammatory response, which  is reflected in  the  dynamics of depression of the  studied  cytokines: simultaneous reduction of proinflammatory cytokines with the limitation of the growth of anti-inflammatory mediators. The final measurements showed a decrease in the content of proinflammatory cytokines: TNFα by 24.6% (p2   < 0.001);  IL-17, by 17.3% (p2   < 0.01);  IL-6, by 20.1% (p2   < 0.001);  IL-1β, by 19.1% (p2   < 0.001), with a decrease in regulatory IL-2  by 25.7% (p2   < 0.001) and anti-inflammatory cytokines IL–10, by 21.3% (p2  < 0.001); Il – 4, by 25.7% (p2  < 0.001); IL-1ra, by 24.4% (p2  < 0.001), when compared to the data obtained with conventional treatment. The  results  obtained allow us to evaluate  this method as highly effective  in the treatment of post-traumatic synovitis,  thus contributing to suppression of inflammatory response  and reduces the secondary alteration of joint tissue structures, preventing the progression of post-traumatic osteoarthritis.